Shadow economies in highly developed OECD countries: What are the driving forces? - Friedrich Schneider; Andreas Buehn (Institute for the Study of Labor (IZA), 2012)
In this paper the main focus lies on 'driving forces' of the development and size of the shadow economy in highly developed 39 OECD countries. The influential factors on the shadow economy are tax policies and state regulation, which, if they rise, increase the shadow economy, but also other factors like economic ones (unemployment) are considered, too. Specifically it is shown that the main driving forces are unemployment, self-employment and the tax burden, which have different weights in these 39 countries. Between 1999 and 2010 indirect taxes have by far the largest relative impact (29.4%), followed by self-employment (22.2%), unemployment (16.9%), personal income taxes (13.1%) and tax morale (9.5%).
Keywords: K42; H26; D78; 330; shadow economy; tax morale; tax pressure; state regulation; undeclared work; Schattenwirtschaft; Arbeitslosigkeit; Selbstständige; Steuerbelastung; OECD-Staaten